Determination of residual mass in left ventricle by intraoperative transesophageal echocardiography after a giant and floating left atrial myxoma resection - Kavakli,Ali Sait (2018)
Abstract Atrial myxoma is a benign tumor of the heart that occurs primarily in the left atrium. Floating or large left atrial myxomas frequently cause functional mitral stenosis, may also affect mitral valve structure and flow, and lead to mitral regurgitation. Systemic embolization occurs in around 30% of cases either from tumor fragmentation or complete tumor detachment hence it should be removed as soon as it is detected. Intraoperative transesophageal echocardiography has a vital importance in the surgery. After resection of myxoma, intraoperative transesophageal echocardiography must be performed to rule out residual mass. The case here reported is of a 48-year old female, who presented with giant and floating left atrial myxoma. Residue mass was detected with intraoperative transesophageal echocardiography in the left ventricle after the resection of myxoma. Subsequently, the residue mass was successfully removed. Complete resection must be required to prevent possible complications such as recurrence, embolization in atrial myxomas. Transesophageal echocardiography performed intraoperatively is vital importance to confirm that the myxoma is completely resected.